2013
DOI: 10.1093/ndt/gft091
|View full text |Cite
|
Sign up to set email alerts
|

Renohepatic crosstalk: does acute kidney injury cause liver dysfunction?

Abstract: The concept of hepatorenal syndrome is well recognized, although incompletely understood. The converse clinical problem of hepatic dysfunction in patients with acute kidney injury (AKI) is less well recognized yet may be a contributor to the high patient morbidity and mortality seen in this group. This review draws together the available evidence for AKI's effect on the liver from animal models, pharmacological studies and recent clinical data. It examines liver function beyond clinically used blood tests, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 111 publications
0
74
0
Order By: Relevance
“…Accumulating clinical evidence has identified a close relationship between renal injury and injuries to other organ systems, including heart, lung, and liver 3. Indeed, impaired liver function is often seen in patients with acute kidney injury (AKI) 4, 5. In addition, in‐hospital death is more likely in patients with AKI and liver failure than in those with AKI alone 6.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating clinical evidence has identified a close relationship between renal injury and injuries to other organ systems, including heart, lung, and liver 3. Indeed, impaired liver function is often seen in patients with acute kidney injury (AKI) 4, 5. In addition, in‐hospital death is more likely in patients with AKI and liver failure than in those with AKI alone 6.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the role of AKI in liver failure is less clear. Some studies suggest a modification of liver metabolism after AKI [35]. In a case-control study in ICU, an increased 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase gene activation in AKI patients compared to control patients without AKI was observed [36].…”
Section: Human Studiesmentioning
confidence: 96%
“…However, RRT is proven to carry dramatic risks for adverse patient outcome leading to the reactive oxygen species as well as, hemodynamic instability and nutrients loss during RRT and inflammatory reaction 64,65 . Depend on the mechanisms mentioned before; several complex pathways are involved in the remote organs injury during AKI including pulmonary, cardiovascular, gastrointestinal, hepatobiliary, and neuromuscular 56,[66][67][68][69] . Remote impact on the heart Acute kidney injury (AKI) may result in acute cardiac disorder via some mechanisms including: and TNFα resulting from increased production and impaired clearance.…”
Section: Remote Organ Injury Following Renal I/r Injurymentioning
confidence: 99%
“…Evidence showed that AKI has significant effect on liver inflammatory response and drug as well as other nutrient metabolism, and even patient outcomes 67 .…”
Section: Remote Impact On the Livermentioning
confidence: 99%